Antimicrobial efficacy of acacia Nilotica (Babul) extract and its effectiveness in disinfecting gutta percha cones - An in vitro study - Dolly R Jagyasi; Neelam D Chandwani; Mohit K Gunwal; Aastha S Ranka (Wolters Kluwer Medknow Publications, 2021)
Background: Gutta-percha cones used directly from the manufacturer's sealed packs harbour micro-organisms. During clinical use, the chances of contamination of gutta-percha increases. Hence, disinfection of gutta-percha cones before use is essential to prevent canal recontamination. Aim: To evaluate the antimicrobial efficacy of babul against chemical disinfectants, and its effectiveness in disinfecting gutta-percha cones. Materials and Methods: The extract of babul was used to assess its antimicrobial activity against E-faecalis, S. aureus and C. albicans using the agar diffusion method. A total of 120 cones acquired from freshly opened manufacturers' pack were cut into three equal parts and divided into group I which was directly placed into a nutrient broth, group II was clinically contaminated with gloves for 30 s and placed into a nutrient broth, and the third part was clinically contaminated with gloves and decontaminated for 5 min using the experimental disinfectants to check for the presence of turbidity. Statistical Analysis: The data were analysed by an Unpaired t-test and Chi-square test at a significance level of P < 0.05 using software SPSS 20. Results: Two percent chlorhexidine showed maximum antibacterial action against E. faecalis and S. aureus followed by babul extract. It was also found more efficacious in decontaminating gutta-percha cones followed by babul and 3% sodium hypochlorite in 5 min. Conclusion: Babul herbal extract is indeed effective in decontaminating gutta-percha cones and is a better alternative to chemical disinfectants.